LACK OF HIGHER EDUCATION IN SOUTH SALMARA MANKACHAR DISTRICT (ASSAM) - Nasif Hoque; M. A. Slet (Galaxy International Interdisciplinary Research Journal, 2022)
Higher education provides people with an opportunity to reflect on the critical, social, economical, cultural, moral and spiritual issues faced by humanity. It contributes to the national development through dissemination of specialized knowledge and skills. Higher education. is a key element in demographic divided and also that it intents to make optimum utilization of human resources specifically in age group from 15-59 years. The condition of higher education is very bad in the South Salmara Mankachar district. Thinking of pursuing higher education is a great sin, that the children had to go to other district on other state for higher education, it is not possible for all the students to study in other district because the economic condition of these people is not so good. In South Salmara Mankachar district only 3 degree colleges exist, Not all subjects are taught in the colleges and if I want to say about professional degree like engineers degree, Master of Business administration, Doctor of Medicine, computer science etc. that there is nothing professional degree here.